2001
DOI: 10.1046/j.1365-3024.2001.00362.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunity to experimental neosporosis in pregnant sheep

Abstract: Neospora caninum is an important cause of fetal loss in cattle but has also infrequently been shown to cause disease in sheep and goats. Experimental infection of pregnant sheep with N. caninum causes clinical and pathological changes very similar to those of neosporosis in cattle. An experiment in sheep was undertaken to examine whether infection with N. caninum before pregnancy conferred immunity to subsequent challenge with the parasite during pregnancy. Primary inoculation of NC1 tachyzoites subcutaneously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0
8

Year Published

2002
2002
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 24 publications
1
30
0
8
Order By: Relevance
“…Repeat abortions in subsequent years have also been reported (Jolley et al, 1999). In addition, studies have shown that experimentally infected sheep will seroconvert and abort in a dose dependent manner (Buxton et al, 1998(Buxton et al, , 2001Weston et al, 2009). These reports suggest that N. caninum infections can and do occur and cause disease, although it has generally not been regarded as a significant cause of abortion in sheep Otter et al, 1997;Buxton et al, 1998;Helmick et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Repeat abortions in subsequent years have also been reported (Jolley et al, 1999). In addition, studies have shown that experimentally infected sheep will seroconvert and abort in a dose dependent manner (Buxton et al, 1998(Buxton et al, , 2001Weston et al, 2009). These reports suggest that N. caninum infections can and do occur and cause disease, although it has generally not been regarded as a significant cause of abortion in sheep Otter et al, 1997;Buxton et al, 1998;Helmick et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Buxton et al (2001) stated that autolysis difficult the histopathological analysis of aborted fetuses' tissues.…”
Section: Discussionmentioning
confidence: 99%
“…(Howe et al, 2012(Howe et al, , 2008Hassig et al, 2003;Kobayashi et al, 2001). Experimental studies have shown that sheep will seroconvert, abort in a dose dependent manner and may have repeated abortions in subsequent pregnancies (Weston et al, 2009;Buxton et al, 2001;Jolley et al, 1999). Nevertheless, the role of N. caninum as a significant pathogen and abortifacient in sheep is still unclear and knowledge about its epidemiology, especially the mode of transmission of neosporosis in sheep, is limited (Helmick et al, 2002;Otter et al, 1997).…”
Section: Introductionmentioning
confidence: 99%